The Development of Booklet Teaching Materials Based on the Learning Cycle 5E Model to Increase Learning Outcomes for X Class Students of SMK BM Panca Budi Medan for the Academic Year 2020/2021 - Rini Siti Jummiah; Saidun Hutasuhut; M. Fitri Rahmadana (Budapest International Research and Critics University, 2021)
The background of the research was the observations regarding the low student learning outcomes because the learning process takes place without a student handbook and the teacher's lack of ability in developing teaching materials so that the learning process still uses the lecture method. Thus, it causes the learning process to be less effective. The purpose of this research was to determine the feasibility of booklet teaching materials based on the learning cycle model developed in accounting subjects for class X SMK BM Panca Budi 2 Medan. The location of the research was at SMK BM Panca Budi 2 Medan, on Jalan Gatot Subroto KM 4,5. The class was class X Accounting for the 2020/2021 Academic Year. This research applied qQuantitative research and developmental (Research and Development) with a 4-D teaching material development model (Four D Model), or 4P by Thiagjaran and Semmel (Trianto, 2013). The 4D development model consists of 4 main stages, namely: (1) define, (2) design, (3) develop, and (4) disseminate. The data analysis technique used was descriptive and inferential techniques. Based on the results of the research, the product of booklet teaching materials based on the learning cycle model in accounting subjects with general journal material in class X SMK BM Panca Budi 2 Medan was feasible to use based on material expert validation with an average of 96.37% design experts, an average of 95, 8% and media experts with an average of 92.9%. Thus, it is suggested to teachers, especially at SMK BM Panca Budi 2 Medan to be more creative in making teaching materials.